Effect of muscle glycogen availability on maximal exercise performance - Hargreaves, M.; Finn, J. P.; Withers, R. T.; Halbert, J. A.; Scroop, G. C.; Mackay, M.; Snow, R. J.; Carey, M. F. (European Journal of Applied Physiology, 1997)
The results would indicate that increased muscle glycogen availability has no direct effect on performance during all-out high intensity exercise.